PENGARUH STRATEGI PEMBELAJARAN E-LEARNING DAN MINAT BELAJAR TERHADAP HASIL BELAJAR AKUNTANSI - Eva Kristiyani; Iffah Budiningsih (Akademika : Jurnal Teknologi Pendidikan, 2019)
The aim of this research is to know the influence of e-learning learning strategy and interest in learning to accounting learning result. This research was conducted at SMK Permata Bangsa Kelurahan Jakasetia, South Bekasi Subdistrict, Bekasi City involving 56 samples taken with random sampling technique to the equivalent class. Instrument used in this research is the accounting test and questionnaire interest in student learning; and the data analysis using two-way ANAVA and Tukey Test. The results of this study obtained: (1) there is a significant difference between the learning outcomes of students who are taught with e-learning learning strategies and expository strategies in which the results of student accounting learning taught by e-learning strategy is higher than the students taught by strategy expository learning. (2) There is an interaction between students who are taught using learning strategies with interest in learning on accounting learning outcomes. (3) This means that the result of group accounting learning which is taught using e-learning learning strategy is significantly higher than that taught using expository learning strategy in students who have high learning interest. (4) While the learning result of student group accounting that is taught using e-learning strategy is same as learning result which is taught using expository learning strategy to students who have low learning interest, influenced by student environment factor and learning design factor in research.